Influence of electric field distortion and i-layer quality on the collection function of drift-driven a-Si:H solar cells - Hof, Ch.; Wyrsch, Nicolas; Shah, Arvind (My University, 2000)
A refined analytical model describing the photocurrent collection in amorphous silicon solar cells is presented. Thereby, variations of the electric field within the intrinsic layer are formally taken into account and it is shown that they can be summarized in a ‘form factor’, φ, which reduces the effective mobility recombination time product of the interior. Based on this model an experimental technique is introduced which aims to determine the transport quality of the intrinsic layer of amorphous silicon solar cells. Two series of cells are analyzed using this technique and the results are compared to transport measurements carried out on equivalent intrinsic layers deposited on glass.